Words matter: judges’ value judgments in sentence pronouncements remarks - de Castro Rodrigues, Andreia (Crime, law and social change, 2023)
This study examines judges’ value judgments on their remarks during sentence pronouncements. We performed a content analysis of 93 sentence pronouncements from the 13 judges from a Portuguese criminal court. Within these discourses, 299 discourse units were codified as judges’ value judgments, that is, personal contents beyond strict legal issues. From these 299, 107 were recommendations (comprehending advice to change, to not reoffend, to rethink life, and action instructions), and 192 were opinions about the individual, the society, and the judicial system. The existence of value judgments in sentence pronouncements carries important implications for the sentencing process. Namely, these value judgments allow the identification of judges’ personal ideas, and issues particularly vulnerable for simplistic reasonings, as well as subjective considerations. This identification and the discussion on the powerful role of language in the context of sentencing are key features to strengthen judges’ training and, consequently, to improve the implementation of penal justice.